Contribution of conspecific negative density dependence to species diversity is increasing towards low environmental limitation in Japanese forests - Pavel Fibich (Nature Portfolio, 2021)
Abstract Species coexistence is a result of biotic interactions, environmental and historical conditions. The Janzen-Connell hypothesis assumes that conspecific negative density dependence (CNDD) is one of the local processes maintaining high species diversity by decreasing population growth rates at high densities. However, the contribution of CNDD to species richness variation across environmental gradients remains unclear. In 32 large forest plots all over the Japanese archipelago covering > 40,000 individual trees of > 300 species and based on size distributions, we analysed the strength of CNDD of individual species and its contribution to species number and diversity across altitude, mean annual temperature, mean annual precipitation and maximum snow depth gradients. The strength of CNDD was increasing towards low altitudes and high tree species number and diversity. The effect of CNDD on species number was changing across altitude, temperature and snow depth gradients and their combined effects contributed 11–18% of the overall explained variance. Our results suggest that CNDD can work as a mechanism structuring forest communities in the Japanese archipelago. Strong CNDD was observed to be connected with high species diversity under low environmental limitations where local biotic interactions are expected to be stronger than in niche-based community assemblies under high environmental filtering.